Degrowth in the suburbs a radical urban imaginary - Alexander, Samuel 1979-; Gleeson, Brendan 1964- (Palgrave Macmillan, 2019)
This book addresses a central dilemma of the urban age: how to make the vast suburban landscapes that ring the globe safe and sustainable in the face of planetary ecological crisis. The authors argue that degrowth, a planned contraction of economic overshoot, is the only feasible principle for suburban renewal. They depart from the anti-suburban sentiment of much environmentalism to show that existing suburbia can be the centre-ground of transition to a new social dispensation based on the principle of self-limitation. The book offers a radical new urban imaginary, that of degrowth suburbia, which can arise Phoenix like from the increasingly stressed cities of the affluent Global North and guide urbanisation in a world at risk. This means dispensing with much contemporary green thinking, including blind faith in electric vehicles and high-density urbanism, and accepting the inevitability and the benefits of planned energy descent. A radical but necessary vision for the times.
Keywords: Suburbaner Raum; Nachhaltigkeit; Stadtentwicklung; Umweltschutz; Klimaänderung; Australien; Stadt- und Regionalsoziologie; Urban Studies/Sociology; Sociology, Urban; Human Geography; Social sciences